Triple-Layer Porous Transport Layers with Ultra-High Porosity for Enhanced Oxygen Transport and Catalyst Utilization in Water Electrolysis - Seong Hyun Park; Young Je Park; Seungsoo Jang; Pilyoung Lee; Soobin Yoon; Young-June Park; Chi-Young Jung; Kang Taek Lee (Nano-Micro Letters)
Highlights A novel triple-layer Ti-porous transport layer (PTL), fabricated using a practical and scalable tape casting and roll calendering process, enhances catalyst utilization by increasing interfacial contact area and the triple-phase boundary. The ultra-high porosity (75%) backing layer and graded structure maximize oxygen transport, mitigate oxygen accumulation, and improve reactant accessibility. Electrochemical evaluations demonstrate a 127 mV reduction in voltage at 2 A cm−2 compared to a commercial PTL, accelerating proton exchange membrane water electrolysis commercialization and supporting the transition to sustainable energy.